Governance for sustainable trade (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Sustainability Impact Assessment is increasingly being used as a tool for assessing the consequences for sustainable development of international trade agreements. While theoretically, Sustainability Impact Assessment can make trade agreements more sustainable, in practice, difficulties are encountered in integrating the assessment findings into decision-making.